2016
DOI: 10.1016/j.chemgeo.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Elemental and isotopic composition of surface soils from key Saharan dust sources

Abstract: Saharan dust contains significant amount of P, an important macronutrient to all living organisms, which has been shown to exert large effects on nearby and remote ecosystems located across the dust transport pathways. The biological effect of Saharan dust depends on the amount and nature of the P speciation of the dust. However, thus far relatively small numbers of samples frompotential source areas (PSA) has been analyzed. Here we report the P speciation (resin-P, HCl-P, Fe-bound-P and organic-P), the 18OP v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
38
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 75 publications
6
38
0
1
Order By: Relevance
“…Our Nd isotopic behavior agrees well with previous reports for summertime Barbados aerosols during 2003-2011 (À14.1 ≤ ε Nd ≤ À11.4; average À 12.7 ± 0.78) (Pourmand et al, 2014). They are also in the range of values reported for the dust derived in North Africa (À17.9 to À10.1) Borg & Banner, 1996;Gross et al, 2016;Grousset et al, 1998;Grousset & Biscaye, 2005;Skonieczny et al, 2011;Skonieczny et al, 2013), over the North Atlantic (À14.2 to À11.2) (Aarons et al, 2013;Grousset et al, 1988), over the Mediterranean Sea (À12.4 to À10.9) (Grousset et al, 1988), and from different locations in the world under the influence of African dust events (À15.3 to À11.1) (Chauvel et al, 2014;Grousset et al, 1988Grousset et al, , 1998Kumar et al, 2014).…”
Section: Sr Nd and Pb Isotopic Variations Between Source And Receptsupporting
confidence: 92%
“…Our Nd isotopic behavior agrees well with previous reports for summertime Barbados aerosols during 2003-2011 (À14.1 ≤ ε Nd ≤ À11.4; average À 12.7 ± 0.78) (Pourmand et al, 2014). They are also in the range of values reported for the dust derived in North Africa (À17.9 to À10.1) Borg & Banner, 1996;Gross et al, 2016;Grousset et al, 1998;Grousset & Biscaye, 2005;Skonieczny et al, 2011;Skonieczny et al, 2013), over the North Atlantic (À14.2 to À11.2) (Aarons et al, 2013;Grousset et al, 1988), over the Mediterranean Sea (À12.4 to À10.9) (Grousset et al, 1988), and from different locations in the world under the influence of African dust events (À15.3 to À11.1) (Chauvel et al, 2014;Grousset et al, 1988Grousset et al, , 1998Kumar et al, 2014).…”
Section: Sr Nd and Pb Isotopic Variations Between Source And Receptsupporting
confidence: 92%
“…However, knowledge about the kinetics of enzyme‐catalysed oxygen isotope exchange is of important value for environmental sciences. The oxygen isotope composition of phosphate has been used as a tracer of sources and processes of phosphorus in aquatic ecosystems, along soil chronosequences and rainfall gradients in terrestrial ecosystems, in arable soils or as a tracer of atmospheric phosphorus inputs to ecosystems . Most studies found that the oxygen isotope composition of bioavailable phosphate in environmental systems is close to equilibrium with the surrounding water.…”
Section: Resultsmentioning
confidence: 99%
“…6) and Sr and Nd signatures measured in aerosols and dust deposits may show contrasted signatures, regarding their departure dust sources (Abouchami et al, 2013). To approximate a representative signature of the regional dust, we only considered aerosols and dust deposits, and selected data from specific regions expected to be dust sources for the study area as it is located along specific wind trajectories: i) the Harmattan deposits in Faya Largeau and Mao in Chad, as well as in N'guigmi and Niamey, Niger (Abouchami et al, 2013); ii) dust deposits in Niamey (Grousset et al, 1998); iii) two soil samples composed mainly of dust from the Bodélé Depression (Gross et al, 2016); and finally, iv) a calculated value for the aeolian end-member that contributed to soils recovered from the Mount Cameroon (Dia et al, 2006). The calculated average value is 0.716 ± 0.001 (n = 8) and − 11.5 ± 1.0 (n = 6) for 87 Sr/ 86 Sr and ε(Nd), respectively, and the Ca/Sr ratio and the Sr/Nd ratio are 179 ± 81 (n = 4) and 3.8 ± 1.6 (n = 6), respectively.…”
Section: Contributions From Allochthonous Sourcesmentioning
confidence: 99%
“…Error bars are the same as symbols. *Average data from Grousset et al (1998), Dia et al (2006), Abouchami et al (2013), and Gross et al (2016). 1 Grousset et al (1998); 2 Grousset et al (1992); 3 Grousset and Biscaye (2005); 4 Bory (1997); 5 Cole et al (2009);6 Skonieczny et al (2011);7 Borg and Banner (1996) Abouchami et al (2013); 10 Pelt et al (2013); 11 Dia et al (2006); 12 Gross et al (2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation